Estimation of Lithium-Ion Battery Health in Electric Bicycles Using Internal Resistance Measurement Method - Saputra, Riza Hadi; Dewanto, Muhammad Ridho; Maulana, Hadi (Faculty of Engineering, Universitas Tanjungpura, 2024)
This study evaluates the performance of a 36 Volt 10 Ah battery in an electric bicycle with a 350-Watt Brushless DC (BLDC) motor as an environmentally friendly alternative to overcome the negative impacts of motorized vehicle use in Indonesia. In addition, this study measured the State of Health battery